(untitled) (Journal of Plant Disease Sciences, 2023)
Leaf scald disease, caused by the fungus Microdochium oryzae, is a devastating and widespread disease of rice. In India, the disease has been linked to yield reductions of up to 23.4%. Aqueous extracts of Acorus calamus, Azadirachta indica, Allium sativum, Sapindus mukorossi, Annona reticulate, Lanatana camara, and Ocimum sanctum at 10% concentration were tested in vitro against Microdochium oryzae. According to the findings, Azadirachta indica extract (71.11%) and Sapindus mukorossi extract (59.0%) were the most efficient phyto-extracts for reducing M. oryzae mycelial growth and were statistically superior to other phyto-extracts. Allium sativum extract ranked in third position in terms of suppressing mycelial growth (47.43%). Ocimum sanctum (39.97%) and Annona reticulate (34.44%), the last two botanicals, were the least effective in preventing M. oryzae mycelial growth. These plant extracts can thus be utilized to combat the rice leaf scalddisease.